PROPOSED BUSINESS MODEL OF COMMERCIAL DIVISION (NON-AERONAUTICAL BUSINESS) AT PT ANGKASA PURA II (PERSERO) (The Indonesian Journal of Business Administration, 2019)
In order to enhance the performance of commercial performance, PT AP II create a unit that handles and controls commercialization activities at PT AP II which was formed in the end of 2017 namely Commercial Division. There are activities related to other units in the process of commercial cooperation including the auction process, space renovation or improvement process, supervision process for the implementation of space renovation or improvement, where the activity is highly dependent on the performance of other units outside the Commercial Division.In this study, the author will analyse the factors that affect the effectiveness of existing business processes in the Commercial Division as the unit responsible for achieving company revenue targets, particularly in the non-aeronautical sector. The challenge that arises in this study is What is the most effective business model can be implemented at the Commercial Division (Non-Aeronautical) of PT AP II.